Efektivitas Peranan Pemerintah Daerah Dalam Merevitalisasi Potensi Objek Wisata di Kabupaten Jeneponto - Muh. Taufik Suni; Dedy Herianto (Politeknik Pariwisata Makassar, Indonesia, 2019)
Jeneponto Regency has various kinds of natural attractions and cultural tourism that can be managed and developed so that it becomes an attractive tourist destination. One of the natural potentials of Jeneponto Regency is bathing in Tamalatea Sub-district called Permandian Birtaria Kassi. The bath was once very crowded but in recent years there has been a drastic decline and has resulted in a decline in tourist interest. This study aims to find out and analyze the effectiveness of the role of the Regional Government in revitalizing tourism in Permandian Birtaria Kassi, Tamalatea Subdistrict, Jeneponto Regency. This research method uses a qualitative descriptive method with a unit of analysis Bathing in Birtaria Kassi, Jeneponto Regency that uses 4 key informants. Oka revealed that there are three aspects in measuring the effectiveness of the government's role in fulfilling tourism facilities and infrastructure, namely Attraction, Accessibility, and Amenities. The results of the study indicate that the role of the government has not been effective in revitalizing the bath of Birtaria Kassi. Therefore, the authors suggest that the regional government of Jeneponto Regency prepare a Human Resource Data Manager who is competent in their fields, allocates a special budget to fix all existing infrastructure shortcomings and the need for cooperation between all stakeholders in maintaining security and comfort for tourists.